Test Sentences: A Linguist's View - Žic Fuchs, Milena (Array, 1995)
This paper analyzes possible inherent flaws in test sentences used for testing psycholinguistic phenomena, more specifically for testing children with special language impairments (SLI). The analysis shows that possible semantic overloading or complexity should be avoided. If the tests are focused on morphology and syntax, then the semantic input should be kept as simple as possible. The downplay of the semantics makes the analysis of morphology and syntax more transparent. In other words, if we want to identify and analyze specific grammatical errors made by a certain population of children, then we should keep the semantics as simple as possible. The reverse is also true, when testing semantic phenomena, grammatical structures should be kept as simple as possible.